Germany and the European research area - Stephanie Daimer; Jakob Edler; Jeremy Howells (Expertenkommission Forschung und Innovation (EFI), 2011)
This report is an account of the relationship between the ERA development and German research and innovation policy (R&I policy). The report introduces what ERA is and how the activities and instruments at European level have fundamentally changed and broadened. It provides a discussion of key initiatives at European level and their interrelation with German R&I policy. In the last decade, and accelerated in the recent years, the European research policy and subsequently the innovation policy have undergone dramatic changes. A range of long-term ambitious initiatives have been developed, most notably within the path-breaking ERA process (research) and the Lisbon strategy (growth). This report addresses these developments by differentiating between traditional (Framework Programme, EUREKA and COST) and new instruments. The new instruments deviate from the classical cooperation funding by addressing either excellence (ERC, EIT) or coordination issues (ETP, ERA-Net). Moreover, also at European level research is no longer a stand-alone approach. Instead, innovation has gained rapidly in importance as a key driver for economic growth. In this report, we present evidence from document analysis and expert interviews for the merit and challenges of the instruments in general and in particular with respect to Germany.
Keywords: 330; Forschung; EU-Forschungspolitik; Technologiepolitik; Forschungskooperation; EU-Staaten; Deutschland